2009
DOI: 10.1007/s10800-009-9832-3
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of oxygen over iron macrocyclic catalysts for DMFC applications

Abstract: The performance of macrocyclic catalysts in oxygen reduction was investigated for a direct methanol fuel cell. The dependence of catalytic activity on different factors was determined for two classes of precursors; namely, iron porphyrin (Fe-PC) and iron phthalocyanine (Fe-TPP). It was found that there was an optimal heattreating temperature for each precursor. Heat-treated Fe-TPP shows maximum activity at 750°C, while the highest performance in the case of Fe-PC is observed at 500°C. It was shown that oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Four years later, Olson and coworkers published a maximum power density of 27 mW cm −2 , with a cobalt-based catalyst at the cathode, at a higher temperature of 70 • C, and methanol concentrations from 0.28 to 4.7 M, with an insignificant variation of voltage-current curves [48]. Almost simultaneously, Serov et al reported DMFC results with a similar power density of 28 mW cm −2 , using an iron-based catalyst at the cathode [45]. The operating temperature in this case was slightly higher, 80 • C, while the methanol concentration was lower (1 M).…”
Section: Review Of Direct Methanol Fuel Cell Performance With M-n-c Cmentioning
confidence: 95%
See 1 more Smart Citation
“…Four years later, Olson and coworkers published a maximum power density of 27 mW cm −2 , with a cobalt-based catalyst at the cathode, at a higher temperature of 70 • C, and methanol concentrations from 0.28 to 4.7 M, with an insignificant variation of voltage-current curves [48]. Almost simultaneously, Serov et al reported DMFC results with a similar power density of 28 mW cm −2 , using an iron-based catalyst at the cathode [45]. The operating temperature in this case was slightly higher, 80 • C, while the methanol concentration was lower (1 M).…”
Section: Review Of Direct Methanol Fuel Cell Performance With M-n-c Cmentioning
confidence: 95%
“…Another class of precursors largely employed for the synthesis of the Fe-N-C or Co-N-C catalysts is based on porphyrins [45][46][47][48][49]. Serov et al [45] synthesized non-PGM catalysts based on M-tetraphenylporphyrin (TPP) (M: Fe, Co, Ni, Cu, Mn, and Zn) and iron phthalocyanine (PC). Kong et al [46] prepared Co-N-C catalysts by mixing etched graphene oxide (GO) sheets with abundant in-plane pores and a porphyrin containing both Co and N elements as the doping precursor.…”
Section: Synthesis Of Noble Metal Free Catalystsmentioning
confidence: 99%
“…On the other hand, CH 3 OH-tolerant catalysts, such as metal phthalocyanines, porphyrins, metal oxides, metal carbides and Ru-based chalcogenides were found to have competitive ORR activity; however, their lifetimes need to be improved [87][88][89][90][91]. Various C-supported binary and ternary alloys of Pt, such as Pt-Co/C, Pt-Cr/C, Pt-Ni/C, Pt-Fe/C and Pt-Cr-Co/C showed better performance compared with Pt/C as cathode catalysts in DMFCs [53,[88][89][90][91][92][93][94][95]. Lee and Popov [96] provided a short review on the catalytic properties of the selected Ru compounds, including crystalline Chevrel-phase chalcogenides, nanostructured Ru and Ru-Se clusters and Ru-N chelate compounds.…”
Section: Electrode Kinetic Limitationsmentioning
confidence: 99%
“…Since metallic macrocycle catalysts are inactive for the electrooxidation of small organic molecules [15,16], they are more suitable to be applied in direct alcohol fuel cells.…”
Section: Evaluation Of Electrocatalytic Activity Of Hm-bp-750 In Dmfcmentioning
confidence: 99%
“…Transition metal macrocyclic compounds are methanol-tolerant [15,16]. When methanol crosses from the anode to the cathode, it does not produce a potential drop with a non-platinum catalyst.…”
Section: Introductionmentioning
confidence: 99%